The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0074-02762007005000109
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral resistance in individuals presenting therapeutic failure and subtypes of the human immunodeficiency virus type 1 in the Northeast Region of Brazil

Abstract: This study aimed to analyze human immunodeficiency virus (HIV) mutation profiles related to antiretroviral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
35
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 34 publications
11
35
0
4
Order By: Relevance
“…The only sequence in the CRF12_BF clade, which was found in a Brazilian man, has the same lineage as the Brazilian sequences. 48,49 The only F1 subtype was detected in a Romanian man, which is consistent with the high percentage of this subtype in this country. 50,51 In summary, the existence of independent monophyletic clades implies the presence of separate transmission networks for non-B subtypes within the population analyzed.…”
Section: Discussionsupporting
confidence: 84%
“…The only sequence in the CRF12_BF clade, which was found in a Brazilian man, has the same lineage as the Brazilian sequences. 48,49 The only F1 subtype was detected in a Romanian man, which is consistent with the high percentage of this subtype in this country. 50,51 In summary, the existence of independent monophyletic clades implies the presence of separate transmission networks for non-B subtypes within the population analyzed.…”
Section: Discussionsupporting
confidence: 84%
“…Most of other Brazilian studies reported NNRTI prevalence of mutations of 30 to 55.4%. 21,23,25,26 In Santos, the overall NNRTI prevalence was not explicit, but K103N occurred in 52% of patients, whereas in these data from Paraná it was 43.4%. 27 At Brazilian Northeast region, the specifi c mutations were even higher, with 62% substitutions in codon 103, 38.7% in codon 190 and 181 in codon 29.2%.…”
Section: Discussionmentioning
confidence: 59%
“…20 The most prevalent mutation occurred at codon 184 (68.31%), as reported in São Paulo (64%), 24 Rio de Janeiro (67%), 23 and Northeast Brazil (66%). 25 In Santos, from 2006, this mutation was even more prevalent (88%). 27 In Paraná, when samples from 2006 were analysed, the prevalence of M184V was of 75%, consistent with the signifi cant increase of lamivudine exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations